A Ni-Zn diatomic electrocatalytic oxygen reduction reaction catalyst and its preparation method and application
By dispersing Ni-Zn diatomic active sites on the nitrogen-doped porous carbon support, an efficient, stable and low-cost Ni-Zn diatom electrocatalytic oxygen reduction catalyst was developed, which solved the high cost of existing platinum-based catalysts and the Fenton reaction problem of Fe-based catalysts, and achieved electrocatalytic performance and better stability comparable to Pt/C catalysts.
Patent Information
- Application Number
- CN202211364120.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-02
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-11-02
AI Technical Summary
The existing platinum-based catalysts have high cost, easy poisoning and undesirable stability in oxygen reduction reactions, which limits their wide application. At the same time, Fe-based catalysts are prone to Fenton reaction with H2O2 during long-term operation, resulting in fuel cell deactivation.
A Ni-Zn diatom electrocatalytic oxygen reduction catalyst was developed to combine a porous carbon support and Ni-Zn diatomic active site by nitrogen-doped, and the preparation method included a sol-thermal reduction method to ensure that Ni and Zn were dispersed on the support in diatomic form.
The high intrinsic activity, good universality, stability and low cost of the catalyst are achieved. The Ni-Zn diatom catalyst exhibits comparable performance to commercial Pt/C catalysts in electrocatalytic redox reactions and remains stable over long-term use.
Smart Images

Figure CN115632134B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of materials and catalysis, and specifically relates to a Ni-Zn diatomic electrocatalytic oxygen reduction reaction catalyst and a preparation method and application thereof. Background Art
[0002] With the continuous development of human society, global CO2 emissions are increasing, which brings about a series of energy and environmental problems. Therefore, it is urgent to find alternative clean energy. Fuel cells, as a clean and pollution-free energy device that can efficiently convert chemical energy into electrical energy under isothermal conditions, have received widespread attention. In energy conversion devices such as proton exchange membrane fuel cells and metal air batteries, the oxygen reduction reaction is usually the rate-controlling step of the entire reaction process. At present, platinum-based catalysts are considered to be the most effective oxygen reduction catalysts, but their high cost, easy poisoning, and undesirable stability limit their widespread application. Therefore, the development of cheap, highly active, and highly durable non-platinum-based catalysts has been a long-standing challenge.
[0003] In recent years, single-atom electrocatalysts have been rapidly developed in the field of energy electrocatalysis due to their highly unsaturated coordination, 100% atomic utilization, and unique electronic structure, especially metal-nitrogen (MN) catalyst structure. Since the N-doped carbon support has high conductivity and can coordinate with metal ligands, the single-atom catalyst of MNC structure has a strong quantum effect. Studies have shown that transition metal-based single-atom catalysts supported on carbon supports have ideal electrocatalytic activity, especially Fe-NC catalysts, which show comparable performance to Pt catalysts in acidic media and have great application potential. Recent studies have shown that bimetallic active centers can further improve catalyst activity and selectivity. For example, N-coordinated Fe-Co bimetallic single atoms have excellent oxygen reduction activity by adjusting the electronic structure and geometric configuration of the active center. However, during long-term operation, Fe-based catalysts are prone to Fenton reaction with byproduct H2O2 to produce a large number of hydroxyl radicals (·OH), which damage the proton exchange membrane and inactivate the fuel cell. Therefore, it is very necessary to develop non-platinum single / double-atom catalysts for non-Fenton processes. Summary of the invention
[0004] The purpose of the present invention is to provide a Ni-Zn diatomic catalyst for electrocatalytic oxygen reduction reaction and its preparation method and application. Not only is the preparation method simple, but the prepared catalyst has high performance, especially high intrinsic activity, good universality, high stability and low price.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] On one hand, the present invention provides a Ni-Zn diatomic electrocatalytic oxygen reduction catalyst, which includes a carrier and an active site. The carrier is a nitrogen-doped porous carbon carrier, and the active site is Ni and Zn. The Ni and Zn are dispersed on the carrier in the form of diatoms, and Ni and Zn are adjacent to each other in space; the active site contains Ni-N and Zn-N coordination.
[0007] In the above technical solution, further, the distance between Ni and Zn adjacent to each other in space is
[0008] In the above technical solution, further, the coordination numbers of the Ni-N and Zn-N are 3-5.
[0009] In the above technical solution, further, the content of Ni in the diatomic material is 0.01-2.0wt%, the content of Zn is 0.01-2.0wt%, and the content of nitrogen is 1-8wt%; the molar ratio of Ni:Zn:N is 1:0.1:10-1:5:500.
[0010] Another aspect of the present invention provides a method for preparing the above-mentioned Ni-Zn diatomic electrocatalytic oxygen reduction catalyst, the method comprising the following steps:
[0011] Step 1, dissolving a Ni metal compound in methanol, and then adding an imidazole organic ligand to obtain a suspension A;
[0012] Step 2, dissolving a Zn metal compound in methanol to obtain a solution B, adding the solution B to the suspension A, stirring, centrifuging, washing with methanol, centrifuging again, drying, and crushing to obtain a precursor C;
[0013] Step 3, placing the precursor C obtained in step 2 into a tubular furnace, introducing an inert gas, calcining, and then naturally cooling to room temperature, and taking out the solid material, which is the prepared catalyst.
[0014] In the above technical solution, further, in step 1, the concentration of the Ni metal compound in the suspension A is 0.001 to 0.2 mol L -1 The concentration of imidazole organic ligand is 0.4~1.0 mol L -1 ;
[0015] The Ni metal compound is nickel acetylacetonate, and the imidazole organic ligand is 2-methylimidazole.
[0016] In the above technical solution, further, in step 2, the concentration of the Zn metal compound in solution B is 0.001 to 0.2 mol L -1 ;
[0017] The Zn metal compound is a nitrate, sulfate or chloride of zinc;
[0018] The stirring time is 5-24h.
[0019] In the above technical solution, further, in step 3, the inert gas is N2 or Ar, and the gas flow rate is 10 to 500 sccm;
[0020] The calcination temperature is 700-1000°C, and the calcination time is 2-6 hours.
[0021] In the above technical solution, further, the molar ratio of the Ni metal compound: the Zn metal compound: the imidazole organic ligand is 1:0.1:20 to 1:5:100.
[0022] In another aspect, the present invention provides an application of the above-mentioned Ni-Zn diatomic electrocatalytic oxygen reduction catalyst.
[0023] The above technical solution is further used to prepare fuel cells and metal-air batteries. The beneficial effects of the present invention are:
[0024] 1. The preparation method of the present invention is simple, and the prepared catalyst has high performance, especially high intrinsic activity, good universality, high stability and low price.
[0025] 2. The Ni-Zn diatomic electrocatalytic oxygen reduction catalyst of the present invention, wherein the Ni-Zn diatoms are distributed in adjacent atomic pairs, and the prepared catalyst shows excellent catalytic performance in the electrocatalytic oxygen reduction reaction.
[0026] 3. The diatomic metal catalyst prepared by the present invention is mainly in an ionic state, the interatomic distance is controllable, the diatomic loading is easy to regulate, and the synthesis method is simple and easy to scale production. The homogeneous diatomic dispersed catalytic material prepared by this method has a catalytic performance in electrocatalytic oxygen reduction comparable to that of commercial Pt / C, and has good catalytic stability, and has strong application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a bright-field phase projection image of the nitrogen-doped carbon-supported NiZn diatomic catalyst of Example 1 using a spherical aberration electron microscope;
[0028] Figure 2 This is a spherical aberration electron microscope high-angle ring dark field image of the nitrogen-doped carbon-supported NiZn diatomic catalyst of Example 1;
[0029] Figure 3 Oxygen reduction polarization curves of the NiZn diatomic catalyst prepared in Example 1 and the commercial 20wt% Pt / C catalyst of Comparative Example 1 in acidic medium;
[0030] Figure 4 The oxygen reduction stability of the NiZn diatomic catalyst prepared in Example 2 in an acidic medium;
[0031] Figure 5 This is the stability of the oxygen reduction stability of the commercial 20wt% Pt / C catalyst in acidic medium in Comparative Example 2. DETAILED DESCRIPTION
[0032] In order to further illustrate the present invention, the following embodiments are listed and described in conjunction with the accompanying drawings, but they do not limit the scope of the invention defined by the appended claims.
[0033] Unless otherwise specified, the methods used in the embodiments are all technical methods well known in the art.
[0034] Example 1
[0035] (1) 0.65 g of nickel acetylacetonate was dissolved in 50 mL of methanol, and then 3.2 g of 2-methylimidazole was added to the methanol solution and stirred at room temperature for 24 h to obtain a suspension A;
[0036] (2) Dissolve 1.47 g zinc nitrate hexahydrate in 50 mL methanol to obtain solution B, add solution B to suspension A, stir thoroughly for 10 h, centrifuge, wash with 100 mL methanol, centrifuge, dry, and crush to obtain precursor C;
[0037] (3) The precursor C obtained in step 2 is placed in a tube furnace, N2 is introduced at a gas flow rate of 100 sccm, the temperature is raised to 700°C, and calcined for 2 hours, and then naturally cooled to room temperature, and the solid material is taken out to obtain the prepared catalyst. Figure 1 and Figure 2 As shown, Ni-Zn diatoms were observed to be uniformly dispersed on the nitrogen-doped porous carbon material under an electron microscope.
[0038] Example 2
[0039] (1) 1.3 g of nickel acetylacetonate was dissolved in 50 mL of methanol, and then 3.2 g of 2-methylimidazole was added to the methanol solution and stirred at room temperature for 24 h to obtain a suspension A;
[0040] (2) Dissolve 2.9 g of zinc nitrate hexahydrate in 50 mL of methanol to obtain solution B, add solution B to suspension A, stir thoroughly for 10 h, centrifuge, wash with 100 mL of methanol, centrifuge, dry, and crush to obtain precursor C;
[0041] (3) The precursor C obtained in step 2 is placed in a tubular furnace, N2 is introduced at a gas flow rate of 100 sccm, the temperature is raised to 700°C, and calcined for 2 hours, and then naturally cooled to room temperature. The solid material is taken out to obtain the prepared catalyst.
[0042] Example 3
[0043] (1) 0.65 g of nickel acetylacetonate was dissolved in 50 mL of methanol, and then 5.2 g of 2-methylimidazole was added to the methanol solution and stirred at room temperature for 24 h to obtain a suspension A;
[0044] (2) Dissolve 2.9 g of zinc nitrate hexahydrate in 50 mL of methanol to obtain solution B, add solution B to suspension A, stir thoroughly for 10 h, centrifuge, wash with 100 mL of methanol, centrifuge, dry, and crush to obtain precursor C;
[0045] (3) The precursor C obtained in step 2 is placed in a tubular furnace, Ar is introduced at a gas flow rate of 100 sccm, the temperature is raised to 800°C, and calcined for 2 hours, then naturally cooled to room temperature, and the solid material is taken out to obtain the prepared catalyst.
[0046] Example 4
[0047] (1) 0.65 g of nickel acetylacetonate was dissolved in 50 mL of methanol, and then 5.2 g of 2-methylimidazole was added to the methanol solution and stirred at room temperature for 24 h to obtain a suspension A;
[0048] (2) Dissolve 2.9 g of zinc chloride in 50 mL of methanol to obtain solution B, add solution B to suspension A, stir thoroughly for 10 h, centrifuge, wash with 100 mL of methanol, centrifuge, dry, and crush to obtain precursor C;
[0049] (3) The precursor C obtained in step 2 is placed in a tubular furnace, Ar is introduced at a gas flow rate of 50 sccm, the temperature is raised to 750°C, and calcined for 4 hours, then naturally cooled to room temperature, and the solid material is taken out to obtain the prepared catalyst.
[0050] Example 5
[0051] (1) 0.65 g of nickel acetylacetonate was dissolved in 50 mL of methanol, and then 5.2 g of 2-methylimidazole was added to the methanol solution and stirred at room temperature for 24 h to obtain a suspension A;
[0052] (2) Dissolve 1.4 g of zinc sulfate in 50 mL of methanol to obtain solution B, add solution B to suspension A, stir thoroughly for 10 h, centrifuge, wash with 100 mL of methanol, centrifuge, dry, and crush to obtain precursor C;
[0053] (3) The precursor C obtained in step 2 is placed in a tubular furnace, Ar is introduced at a gas flow rate of 50 sccm, the temperature is raised to 800°C, and the mixture is calcined for 5 hours, then naturally cooled to room temperature, and the solid material is taken out to obtain the prepared catalyst.
[0054] Test Example 1
[0055] Evaluation of Ni-Zn diatomic electrocatalyst oxygen reduction activity:
[0056] 2.5 mg of the Ni-Zn diatomic catalyst prepared in Example 1 was added to 495 μL of anhydrous ethanol solution, 495 μL of secondary water and 10 μL of a Nafion solution with a mass concentration of 5%, and ultrasonic dispersion was performed for 30 minutes to obtain a dispersed catalyst solution. Then the test was performed in an electrolyte of 0.1M HClO4. The reaction conditions were: 0.1M HClO4 electrolyte, saturated with O2, 5 μL of the dispersed catalyst solution was dropped on a glassy carbon electrode and dried, and a linear sweep voltammetric curve was obtained at 10 mV / s at a rotation speed of 1600 rpm at room temperature.
[0057] Comparative Example 1
[0058] 2.5 mg of commercial 20 wt% Pt / C was added to 495 μL of anhydrous ethanol solution, 495 μL of secondary water and 10 μL of 5% Nafion solution, and ultrasonically dispersed for 30 min to obtain a dispersed catalyst solution. The solution was then tested in an electrolyte of 0.1 M HClO4.
[0059] Figure 3 Oxygen reduction polarization curves of the NiZn diatomic catalyst prepared in Example 1 and the commercial 20wt% Pt / C catalyst in comparative example 1 in acidic medium. As can be seen from the figure, the performance of the NiZn diatomic catalyst is comparable to that of the commercial Pt / C, and the half-wave potential is only about 50mV lower than that of the commercial Pt / C.
[0060] Test Example 2
[0061] Evaluation of the stability of Ni-Zn diatomic electrocatalyst for oxygen reduction:
[0062] 2.5 mg of the Ni-Zn diatomic catalyst prepared in Example 2 was added to 495 μL of anhydrous ethanol solution, 495 μL of secondary water and 10 μL of a Nafion solution with a mass concentration of 5%, and ultrasonic dispersion was performed for 30 minutes to obtain a dispersed catalyst solution. Then the test was performed in an electrolyte of 0.1M HClO4. The reaction conditions were: 0.1M HClO4 electrolyte, saturated with O2, 5 μL of the dispersed catalyst solution was dropped on a glassy carbon electrode and dried, and a cyclic voltammetry curve was obtained at 100 mV / s at 900 rpm at room temperature, and scanned for 10,000 cycles.
[0063] Figure 4 The oxygen reduction stability of the NiZn diatomic catalyst prepared in Example 2 in an acidic medium is as follows: Figure 4As shown, the performance of the NiZn diatomic catalyst remains unchanged after 10,000 cycles of accelerated cycle testing.
[0064] Comparative Example 2
[0065] 2.5 mg of commercial 20 wt% Pt / C catalyst was added to 495 μL of anhydrous ethanol solution, 495 μL of secondary water and 10 μL of Nafion solution with a mass concentration of 5%, and ultrasonic dispersion was performed for 30 minutes to obtain a dispersed catalyst solution. Then the test was performed in an electrolyte of 0.1 M HClO4. The reaction conditions were: 0.1 M HClO4 electrolyte, saturated with O2, 5 μL of the prepared dispersed catalyst solution was dropped on a glassy carbon electrode and dried, and a cyclic voltammetry curve was obtained at 100 mV / s at 900 rpm at room temperature, and scanned for 10,000 cycles.
[0066] Figure 5 For comparative example 2, the stability of commercial 20 wt% Pt / C catalyst for oxygen reduction in acidic medium is shown in FIG. Figure 5 As can be seen from the figure, the performance of 20wt% Pt / C is greatly reduced after 10,000 cycles of scanning test. Figure 4 and Figure 5 The results show that the NiZn diatomic catalyst has better stability than commercial Pt / C in acidic media.
[0067] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. The technicians in the technical field should understand that any improvement of the present invention, the equivalent replacement of the raw materials of the product of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A Ni-Zn diatomic electrocatalytic oxygen reduction catalyst, characterized in that: The catalyst comprises a carrier and an active site, wherein the carrier is a nitrogen-doped porous carbon carrier, the active site is Ni and Zn, the Ni and Zn are dispersed on the carrier in a diatomic form, and Ni and Zn are adjacent to each other in space; the active site contains Ni-N and Zn-N coordination; The content of Ni in the diatomic material is 0.01-2.0wt%, the content of Zn is 0.01-2.0wt%, and the content of nitrogen is 1-8wt%; the molar ratio of Ni:Zn:N is 1:0.1:10-1:5:
500.
2. The Ni-Zn diatomic electrocatalytic oxygen reduction catalyst according to claim 1, characterized in that: The distance between Ni and Zn adjacent to each other in space is 3. The Ni-Zn diatomic electrocatalytic oxygen reduction catalyst according to claim 1, characterized in that: The coordination numbers of the Ni-N and Zn-N are 3-5.
4. A method for preparing the Ni-Zn diatomic electrocatalytic oxygen reduction catalyst according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1, dissolving a Ni metal compound in methanol, and then adding an imidazole organic ligand to obtain a suspension A; Step 2, dissolving a Zn metal compound in methanol to obtain a solution B, adding the solution B to the suspension A, stirring, centrifuging, washing with methanol, centrifuging again, drying, and crushing to obtain a precursor C; Step 3, placing the precursor C obtained in step 2 into a tube furnace, introducing an inert gas, calcining, and then naturally cooling to room temperature, and taking out the solid material, which is the prepared catalyst.
5. The preparation method according to claim 4, characterized in that: In step 1, the concentration of the Ni metal compound in the suspension A is 0.001-0.2 mol L -1 The concentration of imidazole organic ligand is 0.4~1.0 mol L -1 ; The Ni metal compound is nickel acetylacetonate, and the imidazole organic ligand is 2-methylimidazole.
6. The preparation method according to claim 4, characterized in that: In step 2, the concentration of the Zn metal compound in solution B is 0.001 to 0.2 mol L -1 ; The Zn metal compound is a nitrate, sulfate or chloride of zinc; The stirring time is 5-24h.
7. The preparation method according to claim 4, characterized in that: In step 3, the inert gas is N2 or Ar, and the gas flow rate is 10 to 500 sccm; The calcination temperature is 700-1000°C, and the calcination time is 2-6 hours.
8. The preparation method according to claim 4, characterized in that: The molar ratio of the Ni metal compound: the Zn metal compound: the imidazole organic ligand is 1:0.1:20 to 1:5:
100.
9. Use of the Ni-Zn diatomic electrocatalytic oxygen reduction catalyst according to any one of claims 1 to 3.